Nearly common but missed confounder; Sarcoidosis! - Rehana, Kausar (International Journal of Pathology, 2019)
Sarcoidosis is a great masquerader. Its unusual presentations may be completely forgotten. We here describe here a case of sarcoidosis who presented with dermal manifestations of the disease.